A New Analogue of Locked Cyclohexane Nucleic Acids - Šála, Michal; Dejmek, Milan; Procházková, Eliška; Hřebabecký, Hubert; Rybáček, Jiří; Dračínský, Martin; Novák, Pavel; Rosenbergová, Šárka; Rosenberg, Ivan; Nencka, Radim (Synthesis, 2015)
We report on a new analogue of locked cyclohexane nucleic acids that contains an adenine nucleobase at an alternative position and which resembles homo-DNA. The crucial locked carbocyclic nucleoside monomer was prepared with high enantioselectivity and was subsequently incorporated into a pair of modified oligonucleotides that were subjected to hybridization studies.
Keywords: nucleosides; bicyclic compounds; oligonucleotides; carbocycles; medicinal chemistry